2020
DOI: 10.1051/0004-6361/201935815
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength campaign on NGC 7469

Abstract: Aims. We aim to investigate and characterise the photoionised X-ray emission line regions within the Seyfert 1 galaxy NGC 7469. Methods. We applied the photoionisation model, PION, within the spectral fitting code SPEX to analyse the 640 ks reflection grating spectrometer spectrum of NGC 7469 gathered during an XMM-Newton observing campaign in 2015. Results. We find the emission line region in NGC 7469 to be multiphased, consisting of two narrow components with ionisation parameters of log ξ = 0.4 and 1.6. A t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…These researches found that (1) the ultraviolet emissions well correlate with Xray, this is different with Mrk 817; (2) Two absorbers in the ultraviolet band have outflow velocities of ∼ −600 km s −1 and ∼ −2000 km s −1 , and suggested that the low-velocity component located near the broad emission-line region was a highly ionized and high-density absorber, the high-velocity component likely resided farther from the central engine was a lowly ionized and low-density absorber. A parallel but more complicated emission-line region was observed by Grafton-Waters et al (2020).…”
Section: Targetsmentioning
confidence: 57%
“…These researches found that (1) the ultraviolet emissions well correlate with Xray, this is different with Mrk 817; (2) Two absorbers in the ultraviolet band have outflow velocities of ∼ −600 km s −1 and ∼ −2000 km s −1 , and suggested that the low-velocity component located near the broad emission-line region was a highly ionized and high-density absorber, the high-velocity component likely resided farther from the central engine was a lowly ionized and low-density absorber. A parallel but more complicated emission-line region was observed by Grafton-Waters et al (2020).…”
Section: Targetsmentioning
confidence: 57%
“…SED fitting calculations for NGC 5548 performed by different groups using photoionization modeling are in agreement that the corresponding S-curves have prominent TI zones (e.g., Arav et al 2015;Mehdipour et al 2015). The SED found by Mehdipour et al (2015), which has been implemented into CLOUDY (Ferland et al 2017), yields a Compton temperature of T C ≈ 10 8 K. The Compton radius for NGC 5548 is therefore about R IC = 0.2 pc, which is within the inferred distance of the warm absorbers observed in this system (Arav et al 2015;Ebrero et al 2016) and other similar systems like NGC 7469 (e.g., Grafton-Waters et al 2020). It is this correspondence that is suggestive of warm absorbers, which are found in more than half of all nearby AGN (Crenshaw et al 2003), being probes of the multiphase gas dynamics taking place within the thermally driven winds expected at these distances.…”
Section: Introductionmentioning
confidence: 52%
“…where f L is the fraction of the ionizing luminosity being absorbed or scattered by the WA cloud, which is about 2% according to Grafton-Waters et al (2020) and Wang et al (2022) and m p is the mass of proton. The average ionizing luminosity of the sources in our sample is 5 × 10 43 erg s −1 .…”
Section: Resultsmentioning
confidence: 99%